2014
DOI: 10.1021/am405228x
|View full text |Cite
|
Sign up to set email alerts
|

Highly Thermally Stable Single-Component White-Emitting Silicate Glass for Organic-Resin-Free White-Light-Emitting Diodes

Abstract: Thermal management is still a great challenge for high-power phosphor-converted white-light-emitting diodes (pc-WLEDs) intended for future general lighting. In this paper, a series of single-component white-emitting silicate SiO2-Li2O-SrO-Al2O3-K2O-P2O5: Ce(3+), Tb(3+), Mn(2+) (SLSAKP: Ce(3+), Tb(3+), Mn(2+)) glasses that simultaneously play key roles as a luminescent convertor and an encapsulating material for WLEDs were prepared via the conventional melt-quenching method, and systematically studied using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(122 citation statements)
references
References 42 publications
2
120
0
Order By: Relevance
“…QE is defined as the ratio of the number of emitted photons (I em ) to the number of absorbed photons (I abs ), and can be calculated by the following equation [22]. where E R , E S are the spectra of the excitation light without and with the sample in the integrating sphere, respectively, and L S is the luminescence emission spectrum of the sample in the integrating sphere.…”
Section: +mentioning
confidence: 99%
“…QE is defined as the ratio of the number of emitted photons (I em ) to the number of absorbed photons (I abs ), and can be calculated by the following equation [22]. where E R , E S are the spectra of the excitation light without and with the sample in the integrating sphere, respectively, and L S is the luminescence emission spectrum of the sample in the integrating sphere.…”
Section: +mentioning
confidence: 99%
“…QE is an important factor for a phosphor, which is defined as the ratio between the number of emitted photons (I em ) and the number of absorbed photons (I abs ), and can be calculated based on the following Eq.2 [29][30][31]: where L S , E R , and E S are representing the intensity of luminescence emission, the excitation light without and with the sample in the integrating sphere, respectively. Accordingly, the QE value of Li 6 SrLaEuSb 2 O 12 is determined to be 42.46% under 393 nm excitation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated the possibility of color converting materials for full-spectrum white lighting. Zhang et al 43 reported Fig. 3c illustrates the schematic and actual fabrication process of GPPbased wLEDs based on the UV chip-on-board (COB) configuration.…”
Section: Glass Phosphor Plate (Gpp)mentioning
confidence: 99%
“…3c illustrates the schematic and actual fabrication process of GPPbased wLEDs based on the UV chip-on-board (COB) configuration. 43 Zhang et al 44 reported an Eu 2+ -doped silicate SLSAKP GPP, which had a tunable emission band. Gao et al 45 used Al powder to reduce Eu 3+ to Eu 2+ in a SiO 2 -Al 2 O 3 -Na 2 CO 3 -YF 3 -NaF glass matrix.…”
Section: Glass Phosphor Plate (Gpp)mentioning
confidence: 99%